Knowledge and Sugar Sweetened Beverages Consumption Among Adults - Herviana Herviana; Citra Dewi Anggraini; Amalina Rizma; Dedy Siska (International Journal Of Health Science, 2025)
Sugar Sweetened Beverages (SSBs) consumption can tends the risk of health diseases such as obesity, diabetes mellitus type 2, and the risk of cardiovascular disease. One factor that contributes to increasing frequencies of SSBs consumption is individual knowledge. Nutrition knowledge is considered a determinant in decision-making for individual eating behavior or habits. The aim of study was to analyze the relationship between knowledge and the frequency of consumption of SSBs in adult. This study was a quantitative descriptive study with a cross-sectional research design and analyzed data from 158 respondents aged 19-29 years in Kepulauan Riau. Data collection consisted of knowledge about SSBs and the frequency of consumption of SSBs using by Google form. The collected data were analyzed using Spearman’s rank test to examine the relationship between the independent and dependent variables. The results showed that there was no significant relationship between knowledge and the frequency of consumption of SSBs (p = 0.756). Respondents with good knowledge with a frequency of rarely consuming SSBs are 74 respondents (50.3%), but respondents with good knowledge also had a habit of consuming SSBs frequently are 73 respondents (49.7%). However, further research is needed to identify other determinants that influence SSBs consumption.